1988
DOI: 10.1113/jphysiol.1988.sp017240
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and sensitization of fine articular afferents from cat's knee joint by prostaglandin E2.

Abstract: SUMMARY1. In cats anaesthetized with ac-chloralose extracellular recordings were made from fine afferent units belonging to the medial articular nerve of the knee joint. The excitatory and sensitizing effects on articular afferents of prostaglandin E2 (PGE2) applied intra-arterially close to the joint were examined.2. Bolus injections of PGE2 doses of 0-03-30 ,tg excited about 60% of both the group III (conduction velocity 2-5-20 m/s) and the group IV units (conduction velocity < 2-5 m/s). The duration and siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(96 citation statements)
references
References 32 publications
2
91
0
3
Order By: Relevance
“…Conceivably, primary afferent nerve fibers that express TRPV4 as their only mechanical transducer would exhibit properties of silent nociceptors, becoming mechanically responsive only in pathological conditions. Indeed, in parallel to our observations, inflammation induced by carrageenan or by inflammatory soup activates silent nociceptors Schmidt, 1985, 1988a;Xu et al, 2000), but PGE 2 alone is insufficient (Mizumura et al, 1987;Schaible and Schmidt, 1988b;Lang et al, 1990;Grubb et al, 1991;Handwerker et al, 1991;Kress et al, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…Conceivably, primary afferent nerve fibers that express TRPV4 as their only mechanical transducer would exhibit properties of silent nociceptors, becoming mechanically responsive only in pathological conditions. Indeed, in parallel to our observations, inflammation induced by carrageenan or by inflammatory soup activates silent nociceptors Schmidt, 1985, 1988a;Xu et al, 2000), but PGE 2 alone is insufficient (Mizumura et al, 1987;Schaible and Schmidt, 1988b;Lang et al, 1990;Grubb et al, 1991;Handwerker et al, 1991;Kress et al, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…Rather, PGE 2 -evoked hyperalgesia in this model results from a sensitization of the C-fiber terminal, which does not require C a 2ϩ -dependent neurotransmitter release. Sensitization is manifest as a lowered threshold for firing of the terminal; this results in a behavioral allodynia in which non-noxious stimuli can evoke withdrawal reflexes and pain behavior (Martin et al, 1986;Schaible and Schmidt, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin has been shown to bind to B 2 receptors on sensory neurons, resulting in the activation of phospholipase C and ultimately the release of calcium from intracellular stores, thereby triggering neuropeptide exocytosis (Burgess et al, 1989). The pro-inflammatory prostaglandins E 2 and I 2 (PGE 2 and PGI 2 ) have been shown to bind to specific receptors on sensory nerves, where they lower the firing threshold (Schaible and Schmidt, 1988). Recent work has demonstrated that bradykinin and PGE2 have a positive interaction in evoking CGRP release from bovine dental pulp (Goodis et al, 2000).…”
Section: (3) Activation Of Sensory Nervesmentioning
confidence: 99%